Racist extremism in Central and Eastern Europe - Mudde, Cas. (London ; New York : Routledge, 2005)
This handbook on racist extremism in Central and Eastern Europe is the result of a unique collaborative research project of experts from the ten new and future post-communist EU member states. All chapters are written to a common framework, making it easier to compare individual countries.
Bulgaria / Christo Ivanov and Margarita Ilieva -- Czech Republic / Ondřej Čakl and Radek Wollmann -- Estonia / Vadim Poleshchuk -- Hungary / Gábor Bernáth, Gábor Miklósi and Cas Mudde -- Latvia / Nils Muižnieks -- Lithuania / Giedrius Kiaulakis -- Poland / Rafal Pankowski and Marcin Kornak -- Romania / Gabriel Andreescu -- Slovakia / People against Racism, Daniel Milo -- Slovenia / Peace Institute, Tomaž Trplan -- Central and Eastern Europe / Cas Mudde.
Includes bibliographical references and index.
HU OSA 208 - Donation of the Open Society Institute-New York
Keywords: Racism -- Europe, Eastern; Europe, Eastern -- Race relations